Confronting al Qaeda the Sunni awakening and American strategy in al Anbar - Cottam, Martha L.; Huseby, Joe W.; Baltodano, Bruno (Rowman & Littlefield Publishers, 2016)
Based on interviews with tribal Sheiks involved in the Awakening and their American military counterparts, Confronting al Qaeda is a study of decision-making processes and the political psychology of the Sunni Awakening. It traces the change in U.S. military strategy that permitted the collaboration between the Sunni tribes and the U.S. forces.